Veterinary geographic information systems applications in Nigeria: limitations, challenges and needs (2007)
In the developed countries, the application of geographic information systems (GIS) and other geo-information technologies in facilitating epizootiological studies of animal disease outbreaks, disease reporting, monitoring, surveillance, prediction and intervention (prevention, treatment and control) programmes, has been in vogue for decades. Although not yet in the curriculum of any Nigeria’s five veterinary schools. Veterinary geo-information technologies have been promoted and applied at the faculty of Veterinary Medicine, University of Ibadan, Nigeria, since 2001. Limitations encountered in the course of its application include poor rudimentary and inconsistent disease reporting procedures, non-computerised (manual) disease recording techniques, raw unanalysed data, poor information networking, and poor awareness of the role of geo-informatics in veterinary medicine. The major challenge is the development of sufficient and relevant veterinary databases. Major needs include the training and re-training of personnel involved in the use of GIS for veterinary medicine, the acquisition of relevant hardware and software and the funding of a Nigerian unit/centre devoted to GIS application to veterinary medicine. While Nigeria necessarily develops a national (veterinary) spatial infrastructure, multilateral training and funding assistance is needed for a developing country like Nigeria to use developed country geo-information technologies to reduce the impact of animal diseases on animal and human populations.